Using pre-release efficacy as a candidate agent prioritisation tool for the weed Trichocereus spachianus (Caryophyllales: Cactaceae) - T. C. Griffith; M. B. Aguirre; G. F. Sutton; L. Chari; I. D. Paterson (BioControl, 2025)
Pre-release efficacy assessments (PREA) can be used to prioritise the most damaging candidate agents for further studies in biological control programmes against invasive alien plants. This study assessed the efficacy of various potential enemies of Trichocereus spachianus (Riccob.) (Caryophyllales: Cactaceae), an invasive cactus in South Africa, in order to prioritise the most damaging candidates for further studies, including host specificity testing. T. spachianus is considered indigenous in Argentina and Bolivia, but the original description was based on a cultivated plant, and it is either very rare or absent in its indigenous range, with no verified records of natural populations. This necessitates the use of new associations collected off close relatives of the target plant as potential biocontrol agents. We evaluated eight potential biocontrol agents by deriving host suitability indices (HSI) and performing efficacy trials. The HSI analysis demonstrated that only one out of the eight candidate agents, a cochineal insect Dactylopius confertus De Lotto (Hemiptera: Dactylopiidae), had high fitness (high survival, fecundity and complete development) on T. spachianus . This helped us eliminate ineffective agents early on in the programme. The cochineal insect was prioritised for efficacy trials, which demonstrated its high potential efficacy, killing approximately 89% of T. spachianus plants over 60 weeks. Taken together, our results indicated that D. confertus is a highly promising potential agent for the biocontrol of T. spachianus in South Africa. By prioritising candidate biocontrol agents based on efficacy prior to host specificity testing, we ensured that the highest priority candidate agent was identified for detailed and resource-intensive host specificity testing.